FITRAH AKLIYAH DALAM PENDIDIKAN ISLAM - Ahmad Fadlali (Jurnal Forum Tarbiyah, 2009)
Human is being trusted by Allah to be khalifah fi al-ardh by dispositions prearranged to him/her. Among them is fitrah akliyah (thought substance) which differs human from any other Allah’s creatures. In the context of Islamic Education, fitrah akliyah will be consequential if it is utilized and produces three entities. The first is a moslem personality, an integration of human’s spirit, common sense and desire systems that generate behaviors based on Ilahiyah values revealed in the Holy Qoran. The second is to construct contemplation creativeness by admitting children’s potent of creativity, respecting their questions and idea, tackling them to face proactive problems in order to be able to build creativity and imagination. The third is to ponder based on rules that cover the entire mind’s eye of human being’s consideration concerning nature, human and the relationship of human to other creatures.